2006
DOI: 10.1097/01.tp.0000188135.04259.2e
|View full text |Cite
|
Sign up to set email alerts
|

Estimated One-Year Glomerular Filtration Rate is the Best Predictor of Long-term Graft Function Following Renal Transplant

Abstract: The findings of this study corroborate and augment data from previous registry surveys, and confirm the importance of observational studies in investigating the role of peritransplant parameters on long-term graft outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
78
4
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 21 publications
13
78
4
2
Order By: Relevance
“…In spite of the detrimental effect of renal dysfunction in slope analysis, eGFR at first observation correlated significantly with that at last observation, confirming the notion [24,25] that early kidney function is a useful surrogate marker for graft outcome.…”
Section: Discussionsupporting
confidence: 70%
“…In spite of the detrimental effect of renal dysfunction in slope analysis, eGFR at first observation correlated significantly with that at last observation, confirming the notion [24,25] that early kidney function is a useful surrogate marker for graft outcome.…”
Section: Discussionsupporting
confidence: 70%
“…Data from a multicenter study pointed the 1 year estimated glomerular filtration rate to be the most relevant predictor of long term graft function. The impact of DGF and acute rejection on the long term graft function appeared to be fully mediated by their influence on the 1 year GFR (Salvadori et al, 2006). Similar to us, three studies found allograft function at 1 year to be a significant and independent predictor of graft outcome in children (Filler et al, 2002;Mitsnefes et al, 2003;Muscheites et al, 2009).…”
Section: Discussionsupporting
confidence: 65%
“…387 In addition, several analyses have suggested that renal function at 1 year post transplant is a good predictor of long-term graft survival. 334,340,[388][389][390] Throughout this section it should be noted that graft survival and failure does not include DWFG, that is, considering only people who are alive and who become dependent on dialysis or require retransplantation.…”
Section: Estimation Of Graft Survivalmentioning
confidence: 99%